(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Recently, there have been significant developments in inkjet printing for applications in various fields such as medicine, biomaterials and sensors. In this research, enzymes like horseradish peroxidase (HRP) and glucose oxidase (GOx) were directly printed by inkjet printer onto flexible textile fabric in predefined patterns to produce a functional material. The functionality of the printed enzymes (bioink) was investigated by chemical reaction after printing fresh and stored bio-ink in a digital printer. The results indicated that these enzymes can be effectively printed individually or in combination, which retains their functionality after printing. Furthermore, HRP was coupled and printed with fluorescent group, the result confirmed that the printed enzyme was still active and retained its functionality despite the printing process. Hence, the digital printing technique can be used as a novel method for producing functional textiles for advanced applications in monitoring health and security.